On the solution of a finite element approximation of a linear obstacle plate problem - Fernandes, Luis M.; Figueiredo, Isabel N.; Júdice, Joaquim J. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper the solution of a finite element approximation of a linear obstacle plate problem is investigated. A simple version of an interior point method and a block pivoting algorithm have been proposed for the solution of this problem.
Keywords: variational inequality; complementarity problem; contact problem